The influences of service marketing mix on customer loyalty towards Umrah travel agents: Evidence from Malaysia - Bestoon Abdulmaged Othman; Amran Harun; Wirya Najm Rashid; Safdar Nazeer; Abdul Wahid Mohd Kassim; Kadhim Ghaffar Kadhim (Growing Science, 2019)
In the Malaysian Umrah industry, there are so many new entrants selling and offering similar products and services. As a result, Umrah providers must compete to survive in the Umrah travel industry, as there are currently so many competitors. They need to focus on customers’ special needs and preferences to maintain the long-term relationship. Hence, the purpose of this research is to identify the relationship between service marketing mix and customer’s loyalty towards Umrah travel agents in Malaysia. The customers who performed Umrah more than once were on the focus of this study. The necessary data were collected from 384 respondents through a structured questionnaire using a convenience sampling technique. The results of the research confirm that all “service marketing mix” elements (“price, product, place, promotion, process, people, and physical evidence”) show significant positive effects on customer loyalty. This study will be of interest to the Umrah travel industry in understanding how marketing mix strategies are essential for maintaining a long term relationship with customers.